Multilevel Impacts of Transformational Leadership on Service Quality: Evidence From China - Su, Fangguo; Cheng, Dejun; Wen, Shanshan (Frontiers in Psychology, 2019)
In service contexts, leaders’ efforts to maintain and enhance employees’ service quality are vital to organisational performance. However, few studies have investigated the mechanisms underlying the relationship between transformational leadership (TFL) and employees’ service quality across levels. Based on the theory of planned behaviour, this study investigated the multilevel impacts of TFL on employees’ service quality and the multilevel mechanisms mediating this relationship. Data were collected from 208 managers and 1,431 employees at 223 branches (chain restaurants) of a large catering corporation in southern China. The results showed that stronger TFL significantly improved employees’ service quality at both individual and branch level. Affective commitment and psychological empowerment partially mediated the relationship between individual-level TFL and employees’ service quality. Branch-level service climate fully mediated the relationship between branch-level TFL and employees’ service quality.